Jiedu Xiaozheng Decoction Augments 5-fluorouracil Induced Anti-hepatic Carcinoma Effect in Vitro and in Vivo - Zhiyun CAO; Liangpu ZHENG; Wei LIN; Xuzheng CHEN; Xiaoqin ZHU; Jiumao LIN; Wei LIN; Jian DU (康复学报)
Objective:Up to now, morbidity and mortality of hepatocellular carcinoma(HCC)have been increasing all over the world especially in China.5-fluorouracil(5-FU)is a common used chemotherapy drug for many types tumor in clinic including HCC. However with the bigger dosage of 5-FU applying the more severely toxicity and side-effects have limited it's widely clinical use. Therefore, there is a strong demand to find some new drugs of low side-effect for HCC treatment. Accumulating attention has been paid to Traditional Chinese Medicine(TCM)because of the multi-targets, low-toxicity and the whole system regulation for patients. Maybe it is a potential effective way on finding some TCM to enhance anti-tumor effect with low dose 5-FU.Jiedu Xiaozheng Decoction(JXD), a polyherbal formula of TCM, has been used in clinical treatment for digestive tract tumor especially HCC for more than a decade. The previous studies found that JXD inhibited tumor growth by inducing apoptosis, blocking cell cycle and anti-angiogenesis. In this study, we evaluated anti-cancer effects of JXD ethyl acetate extract(EE-JXD)combined with 5-FU in vitro and in vivo in order to explore the biological mechanism and provide more experimental basis for clinical application of JXD.Methods：EE-JXD was prepared according to the describe in the previous study. Then EE-JXD was diluted to 200 mg/mL with dimethyl sulfoxide for in vitro experiment and was dissolved in normal saline to a final concentration of 6 mg/mL in vivo study. HepG2 cell line was cultured in RPMI-1640 medium supplemented with 10%fetal bovine serum, 1%penicillin and streptomycin at 37℃in an incubator containing 5%CO2.In vitro, cells viability was detected by MTT assay after HepG2 cells were treated with different concentrations of EE-JXD(0.05, 0.1, 0.2, 0.4 mg/mL), 5-FU(0.05, 0.1, 0.2, 0.4 mg/mL), and EE-JXD+5-FU(0.05+0.05, 0.1+0.1, 0.2+0.2, 0.4+0.4 mg/mL)for 24 hours. And then the HepG2 cells were divided into control group, EE-JXD group(0.1 mg/mL), 5-FU group(0.1 mg/mL)and EE-JXD+5-FU group(0.1 mg/mL+0.1 mg/mL). Cells apoptosis of four groups were evaluated by fluorescence assay and flow cytometry respectively after treated for 24 hours. In fluorescence assay, the HepG2 cells were stained with Hoechst 33258 at room temperature and apoptosis was observed under a fluorescence microscope. The treated HepG2 cells were processed and analyzed using an Annexin V-FITC/propidium iodide(PI)assay with flow cytometry for quantitative determination of early and late stage apoptotic cells. Thirty-two male BALB/c(nu/nu)mice(body weight, 18-22 g)were used to establish the subcutaneous xenotransplanted tumor model of HepG2 cell line. HepG2 cells in density of 5×106cells/mL were subcutaneously injected in the right flank of each mouse. After seven days thirty-two mice were randomly assigned to four groups: EE-JXD group, administered 15 g/(kg·d)EE-JXD(i.g.);5-FU group, administered 10 mg/(kg·d)5-FU(i.p.), a low dose confirmed by pre-experiment;EE-JXD+5-FU group, administered 15 g/(kg·d)EE-JXD and 10 mg/(kg·d)5-FU;and control group(normal saline).Tumor volume and body weight were measured every three days. Tumor weight was weighed after the tumor was stripped at day 30. The apoptosis rate of tumor was evaluated by terminal dexynucleotidyl transferase(TdT)-mediated dUTP nick end labeling(TUNEL).Results：EE-JXD, 5-FU and EE-JXD+5-FU inhibited proliferation of HepG2 cells in a concentration-dependent manner. The combination of JXD and 5-FU had a strong inhibitory effect on the proliferation of HepG2(P<0.01, compared with the control group). Apoptosis was obvious in both 5-FU and EE-JXD groups in fluorescence assay. Apoptosis were enhanced when EE-JXD combined with 5-FU.Further assay using Annexin V-FITC/PI double staining showed HepG2 cells treated with 5-FU, EE-JXD and EE-JXD+5-FU to induce apoptosis in 5%, 7.8% and 12.9% after 24 hours. In contrast, mice treated with either 5-FU, EE-JXD or 5-FU plus EE-JXD showed slower progression of established tumors. Control mice reached a total tumor weight of(0.43±0.06)g within 30 days. At this time point, the tumor weight of mice treated with 5-FU was significantly smaller(P<0.01)at(0.08±0.01)g. Significant slowdown in tumor progression compared with control mice was observed in the group of mice receiving 5-FU and EE-JXD, reaching only(0.05±0.01)g tumor volume with in 30 days(P<0.01).During 30 days' treatment, the body weight between the control group and the treatment groups were similar(P>0.05). Apoptosis index was significantly higher in the 5-FU group compared to the control group(P<0.05), and was further increased when EE-JXD combined with 5-FU(P<0.01).Conclusion：The present study shows that low-dose 5-FU combined with EE-JXD has a strong anti-cancer effect than 5-FU alone. The effect is more obvious in vivo than in vitro experiments. No adverse events appeared in mice treated with both 5-FU and EE-JXD, indicating that 5-FU combine with EE-JXD at the indicated dose is safe. The results suggest that EE-JXD may potentially be combined with 5-FU for HCC and warrants additional investigation.